Studi Penokohan dalam Novel Moga Bunda Disayang Allah Karya Tere Liye - Resti Andini; Liza Septa Wilyanti; Nurfadilah (Jurnal Riset Rumpun Ilmu Bahasa, 2026)
This research is motivated by the importance of studying characterization in novels as a means of understanding human values ​​and character education relevant to social reality. Tere Liye's novel "Moga Bunda Disayang Allah" presents characters with complex characters that reflect empathy, compassion, and struggles facing limitations and social stigma. This study aims to comprehensively describe the characterization contained in the novel. The method used is a qualitative descriptive method with a structural literary analysis approach, specifically Nurgiyantoro's characterization theory. The research data, consisting of narrative excerpts and dialogues depicting the characters' characters, were collected through reading and note-taking techniques. Then, they were analyzed based on the categories of main and supporting characters, protagonist and antagonist, simple and round characters, static and developing characters, and typical and neutral characters. The results show that this novel displays diverse and dynamic characterization, with most of the characters experiencing significant character development and playing a crucial role in conveying moral values. The implications of this research are expected to enrich the study of Indonesian literature and be used as an alternative teaching material in character education-based literature learning.